ANALISIS PENGARUH KUALITAS PRODUK, PROMOSI, DAN TENAGA PENJUAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK IMPORT ORIFLAME DI SPO 1507 - Hasibuan, Reza Rahmadi (JURNAL EKONOMI, 2021)
The purpose of this study to examine the influence of analysis of effect of quality products, promotions and seller performance to decision of purchase of import oriflame cosmetic products in SPO 1507. The results obtained show that the quality of product has a significant effect on purchasing decisions, this can be proven by the sig value. count smaller than 0.05 ie 0.013 <0.05. Promotion has a significant effect on purchasing decision, this can be proven with sig value. count smaller than 0.05 ie 0.017 <0.05. Salespeople have no significant effect on purchasing decisions, this can be proven by the sig value. the count is greater than 0.05 ie 0.145> 0.05. The quality of prodak, promotion and salespeople has a proportion of influence on the purchase decision of 26% while the remaining 74% is influenced by other variables that are not in the linear regression model. Keywords: prodak quality, promotion, salesman and purchase decision.